Identifying and exploring linguistic expertise of psychiatrists in interviews with patients with thought disorder. (April 2020) - Galletly, Cherrie; Ash, David; Sweeney, Shaun; O'Neill, Fiona; Crichton, Jonathan
Objective: To identify and understand the linguistic expertise of psychiatrists in clinical interviews with patients experiencing thought disorder (TD). Method: Qualitative analysis of 24 routine clinical interviews between psychiatrists and inpatients with TD. Results: Psychiatrists demonstrated the expertise with which they navigated clinical interviews and accomplished shared goals with patients experiencing TD. These findings highlight the need to rethink the notion that such patients are incapable of productive communication. Capturing and describing psychiatrists' tacit expertise provides a foundation for documenting an under-recognised skill set. Conclusions: Understanding such expertise could enhance the care of patients with TD, repositioning them as active participants in the accomplishment of shared therapeutic goals. Teaching these skills to mental health clinicians during their training would improve their ability to establish effective therapeutic relationships with these patients.